Historical Review of the Role of Saparua Chinese in the Spice Trade from the Colonial to the Reformation - Sari, Risa Junita; Nugraha, M. Satria; Ersi, Livia; Yulia, Refni (Manunggal Halim Jaya, 2026)
This study analyzes the role of ethnic Chinese in the island of Saparua's spice trade. Spices are among the trade commodities with the highest prices. For decades, Chinese traders have been among the distributors of Asian spices to Europe. The progress of maritime routes also affected spice trade activities in the archipelago. In the 16th century, Europeans such as the Portuguese were directly involved in the trade in the Maluku, followed by a trade monopoly by Dutch companies. With the times, spices are no longer a priority in international trade. So, after independence, until the reform of spice prices, it experienced ups and downs. During the colonial government until the reform, Chinese traders played a vital role in the spice trade, especially on Saparua Island. It is necessary to analyze the role of ethnic Chinese in the island of Saparua's spice trade during the colonial and reform periods. Through a historical review using historical methods, from source collection to criticism, interpretation, and historiography, it was found that the role of Chinese traders in Saparua was as merchants as well as channels or distributors between local traders and buyers outside the island.